Legal and contitutional analysis of the obligation to provide safe work environment in the chilen law within the social protection - Ravinet Muñoz, César (Derecho Público Iberoamericano, 2020)
Every so often, legal issues stemming from health and safety regulations appear, yet these are not always fully addressed. After the widely-known accident of the 33 trapped miners in Chile, this decisive event, for a while switched the focus to the obligation for employers to provide workplace safety. Recently, a new law has come to force, which obliges independent workers to join the Social Security System. This means that more than 500.000 workers will be part of the current system. Therefore, legal health and safety issues are being debated once again. This article describes firstly a general view on how this obligation inserts in our legal system and how it is linked to constitutional rights. Secondly, an analysis as key element of the social security system and its link to the occupational accidents and work-related diseases insurance established by the law number 16.744. [...]